Feeding Modalities and the Onset of the Neonatal Abstinence Syndrome - Anthony eLiu; Jamie eJuarez; Ajitha eNair; Ralph Kay Heinrich Nanan (Frontiers Media S.A., 2015)
AbstractBreast milk has been reported to ameliorate the severity and outcome of neonatal abstinence syndrome (NAS). The mechanism of this beneficial effect of breast milk on NAS remains unclear, as the negligible amount of methadone transmitted via breast milk is unlikely to have an impact on NAS. The aim of this study was to compare the impact of different feeding modalities on the onset of NAS.A retrospective medical record review was conducted on one hundred and ninety-four methadone maintained mother/infant dyads. Infants were categorized on the first 2 days of life as predominantly breastfed, fed expressed human breast milk or formula fed. The feeding categories were then analyzed using the onset of NAS as the outcome measure. After adjusting for confounders, there was no significant effect of the modality of feeding on the rates of NAS requiring treatment (p=0.11). Breastfeeding significantly delayed the onset of NAS (p=0.04)The act of breastfeeding in the first two days of life had no effect on whether an infant required treatment for NAS when compared to those fed EBM or formula. This only suggests that the advantages of breastfeeding on NAS cannot be substantiated in a small cohort and should not discourage breastfeeding.